Development of smart shading device for dynamic daylighting and solar control in tropical climate - Ahmad, Mohd. Hamdan (2012)
Daylight is dynamic, thus there is no one common solution for all scenarios. It is more critical in tropical climate where the sky is predominantly intermediate; with inconsistent clouds formations which will influence the presence of direct sunlight and daylight availability.